Asthma—The Physiological and Clinical Spectrum in Childhood: Respiratory Function Studies in its Assessment. Issue 256 (December 1972) - Hill, D. J.; Landau, L. I.; McNicol, K. N.; Phelan, P. D.
Abstract : Tests of respiratory function based on spirometry have hitherto proved of limited value in the assessment of asthmatic children in the interval phase. In an attempt to provide more information on this subject, respiratory function studies using a body plethysmograph were carried out in 106 asthmatic children aged 13 to 15 years during an asymptomatic period. The children were selected to cover the whole spectrum of asthma in childhood; they were divided into 4 grades on clinical criteria, and the results of the physiological studies compared with the clinical gradings. Results indicated that maximum expiratory flow volume curves, when combined with an estimation of lung volumes, provided the best assessment of the severity of a child's asthma. Using this test of respiratory function, most children in whom asthma had been a trivial complaint had virtually no abnormality, but a small number had mild airways obstruction. Those with chronic continuing asthma had evidence of severe airways obstruction and pulmonary hyperinflation. In children with episodic asthma, the degree of abnormality was variable and the frequency of the attacks seemed to be a major factor in determining this. It is concluded that respiratory function studies are a valuable tool in evaluating asthma in childhood, particularly when the clinical history is difficult to assess.